2020
DOI: 10.1017/s0954579420001327
|View full text |Cite
|
Sign up to set email alerts
|

Environmental determinants of physiological reactivity to stress: The interacting effects of early life deprivation, caregiving quality, and stressful life events

Abstract: Children who spend their early lives in institutions experience profound psychosocial deprivation that is associated with altered stress response system development. Here, we used data from a longitudinal randomized controlled trial of foster care for institutionally reared children to examine whether caregiving quality and stressful life events (SLEs) in early adolescence (age 12) influence patterns of hypothalamic–pituitary–adrenal (HPA) axis and sympathetic nervous system (SNS) reactivity. Controlling for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 61 publications
3
10
0
Order By: Relevance
“…For example, in the BEIP, institutionally reared children randomly assigned to family-based foster care in childhood were less responsive to the effects of stressful life events during adolescence on externalizing problems, while those with prolonged deprivation showed an increased risk of externalizing problems (Wade, Zeanah, et al, 2019). Similar buffering effects of family care have been demonstrated for markers of low-grade inflammation (Tang et al, 2020) and physiological reactivity to social stress (Wade, Sheridan, et al, 2020), with forthcoming evidence that these effects also manifest for behavioral and neural markers of cognitive control (Wade et al, 2021). Although we suspect that these results showcase the buffering effect of family-based stimulation following deprivation, it is important to note that the advent of entry into foster care from institutional care may be associated with increases in both stimulation and sensitivity, as well as enhanced stability (described below).…”
Section: Stimulationmentioning
confidence: 69%
See 1 more Smart Citation
“…For example, in the BEIP, institutionally reared children randomly assigned to family-based foster care in childhood were less responsive to the effects of stressful life events during adolescence on externalizing problems, while those with prolonged deprivation showed an increased risk of externalizing problems (Wade, Zeanah, et al, 2019). Similar buffering effects of family care have been demonstrated for markers of low-grade inflammation (Tang et al, 2020) and physiological reactivity to social stress (Wade, Sheridan, et al, 2020), with forthcoming evidence that these effects also manifest for behavioral and neural markers of cognitive control (Wade et al, 2021). Although we suspect that these results showcase the buffering effect of family-based stimulation following deprivation, it is important to note that the advent of entry into foster care from institutional care may be associated with increases in both stimulation and sensitivity, as well as enhanced stability (described below).…”
Section: Stimulationmentioning
confidence: 69%
“…For example, in the BEIP, caregiving stability appears to promote at least partial recovery in domains such as mental health and executive functioning following extreme neglect and deprivation (Humphreys et al, 2020; Wade, Zeanah, et al, 2020). In contrast, the buffering effect of caregiving quality against exposure to severe deprivation appears to be less pronounced for markers of stress response system function (Wade, Sheridan, et al, 2020). Thus, while the presence of resilience-promoting factors may preserve function or facilitate recovery to a degree, some residual difficulties may persist that require more targeted intervention or social programming.…”
Section: Discussionmentioning
confidence: 99%
“…The first is stress reactivity, where we have shown that children in the FCG demonstrated a level of neuroendocrine and sympathetic reactivity to social stress at 12 years that resembles children in the NIG, especially when foster placement occurred prior to age 24 months (McLaughlin et al, 2015). In contrast, children in the CAUG demonstrated persistently blunted reactivity to social stress (also see Wade, Sheridan, et al, 2020), strongly suggesting a sensitive period for recovering the adaptive stress response early in development. Moreover, this may have consequences for how these individuals respond to stressors during adolescence.…”
Section: Mechanisms Of Recovery Following Family‐based Carementioning
confidence: 99%
“…Many children in orphanages suffer from attachment and behavioural problems like internalizing problems such as depression, anxiety and social withdrawal and externalizing problems such as aggression, defiance, hostility and poor impulse control (Adler et al, 2020; Brown et al, 2015; Huffhines et al, 2020) . Due to the lack of knowledge, children’s behaviour is often misunderstood by caregivers, which in turn can lead to more maltreatment of children (Smyke et al, 2002; Wade et al, 2020). Violent disciplinary methods are extremely widespread and due to their social acceptance, caregivers’ positive attitudes towards such methods, and lack of caregiver knowledge they are the most common form of violence experienced by children (Lansford et al, 670; UNICEF, 2010, United Nations Children’s Fund, 2014).…”
Section: Introductionmentioning
confidence: 99%